PECULIARITIES OF THE FUNCTIONING OF DOMESTIC ELITE INSTITUTIONS OF HIGHER EDUCATION - Machynska, Nataliia; Blikhar, Viacheslav (Socio-economic relations in the digital society, 2024)
The article provides a theoretical and practical analysis of the problem of the formation and development of elite higher education in Ukraine. In the context of the specified problem, the authors singled out: trends in the activity of educational institutions in the conditions of a full-scale invasion of Russia; factors of increased interest of researchers in studying the problem of elites, elite thinking, elite educational institutions; growth trends of private educational institutions in Europe and Ukraine. An analysis of different approaches to the interpretation of the concepts of "elite", "private school", "alternative educational institutions", "elite education", "elite university", etc. is offered. The authors proposed a description of different types of private schools, in particular, elitist, denominational, compensatory, conjunctural, national and alternative models. The article presents the classification of private schools (preschool, primary, day, non-formal, with moderate and high tuition fees, with historically developed traditions and modernity, etc.), and highlights their characteristic features. A comparative analysis of research and elite universities was partially carried out, and the characteristic features of a research university were singled out and characterized (the multi-functionality of the institution, the presence of a system of training specialists with a scientific degree, a wide selection of specialities and specializations, the formation of an intellectual environment around the university, a competitive and selective approach to the selection of students; the presence of corporate ethics, etc.). The article focuses on the specific characteristics of elite universities (autonomy, compactness, own traditions, small numbers, etc.), highlights the most significant factors of the emergence and development of elite higher education institutions in Ukraine (growing demand of the population for appropriate education, creation of an appropriate educational environment, expanded network of social provision of the most gifted students, etc.).